2011
DOI: 10.1007/s10397-010-0643-7
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of sexual function after transobturator tape procedure in women with stress urinary incontinence

Abstract: Sling procedures are a widely proven treatment for stress urinary incontinence. The aim of this prospective study was to evaluate the effect of the transobturator tape on female sexual functioning. Fifty-four women treated for stress urinary incontinence with transobturator tape filled out self-administered questionnaires on quality of life, urinary incontinence, and sexual function prior to surgery and 6 weeks and 12 months postoperatively. Preoperatively, 40 women (78%) were sexually active. There were no si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…It is also speculated that after the TOT procedure, damage to vascular and neural structures may lead to sexual dysfunction [29]. On the other hand, in other tudies, it is suggested that due to the anatomic route of the TOT procedure, there are no effects on major neurovascular structures and therefore there is no effect on sexual functions [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also speculated that after the TOT procedure, damage to vascular and neural structures may lead to sexual dysfunction [29]. On the other hand, in other tudies, it is suggested that due to the anatomic route of the TOT procedure, there are no effects on major neurovascular structures and therefore there is no effect on sexual functions [38].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of coital incontinence ranges from 10 to 56% [27,28]. Arts-de Jong et al [29] evaluated the effect of TOT on female sexual functions. There were no significant postoperative changes regarding frequency of sexual activity, sexual desire, and problems with lubrication or orgasm.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, in a prospective 12‐month follow‐up study, Arts‐de Jong et al. reported significant improvements in pain scores (during or after sexual activity) after TVT‐O. In addition, we used the PISQ‐12 to evaluate sexual function pre‐ and postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have demonstrated sexual function improvement. Arts-de Jong et al found significant improvement in satisfaction regarding sexual function at 1 year (20). In our study, we asked the patients 19 questions about sexuel function.…”
Section: Discussionmentioning
confidence: 79%